VARIATION OF IMPACT TOUGHNESS OF AS-BUILT DMLS TI6AL4V (ELI) SPECIMENS WITH TEMPERATURE - Muiruri, Amos Mwangi; Maringa, M; du Preez, WB; Masu, LM (The South African Journal of Industrial Engineering, 2018)
The response of direct metal laser sintering (DMLS) produced Ti6Al4V (ELI) to impact was investigated using an instrumented Charpy impact test machine and V-notch specimens. Impact toughness testing was conducted over the temperature range of -130oC to 250oC. The effect of the orientation of the V-notch, with reference to the base plate, was investigated. The results indicated that the samples that were produced with the V-notch facing the base plate (LO) had better values of impact toughness than those that were produced with the V-notch facing away from the base plate (UP) over most of the test temperatures. The study further established that as-built DMLS Ti6Al4V (ELI) retains appreciable notch toughness, even at extremely low temperatures